First-Generation College Students' Mental Health During the COVID-19 Pandemic. Issue 2 (4th May 2022) - Soria, Krista M.; Kelling, Christine; Mossinghoff, Melissa; Beahm, Robyn
ABSTRACT: We analyzed data from 7, 269 first-generation college students enrolled at nine large, public research-intensive universities who completed the Student Experience in the Research University (SERU) COVID-19 survey. In our sample, 40.3% of first-generation students experienced clinically significant symptoms of major depressive disorder (MDD) and 44.6% experienced clinically significant symptoms of generalized anxiety disorder (GAD)—figures higher than national averages. We discuss several individual, interpersonal, institutional, health and safety, and academic and financial stressors that were associated with first-generation students' clinically significant MDD and GAD symptoms.